2001
DOI: 10.1038/88107
|View full text |Cite
|
Sign up to set email alerts
|

Creation of genome-wide protein expression libraries using random activation of gene expression

Abstract: Here we report the use of random activation of gene expression (RAGE) to create genome-wide protein expression libraries. RAGE libraries containing only 5 x 10(6) individual clones were found to express every gene tested, including genes that are normally silent in the parent cell line. Furthermore, endogenous genes were activated at similar frequencies and expressed at similar levels within RAGE libraries created from multiple human cell lines, demonstrating that RAGE libraries are inherently normalized. Pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Whether the regulation of expression of these genes is aected in this tumour by the viral integration is unclear. Interestingly, the cellular sequence identi®ed in tumour number 3 is part of an expressed gene (Harrington et al, 2001). It is very likely that the integration event in this case has disrupted a gene.…”
Section: Discussionmentioning
confidence: 95%
“…Whether the regulation of expression of these genes is aected in this tumour by the viral integration is unclear. Interestingly, the cellular sequence identi®ed in tumour number 3 is part of an expressed gene (Harrington et al, 2001). It is very likely that the integration event in this case has disrupted a gene.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, PNPLA1 has yet to be assessed for enzymatic activities, and the only evidence we are aware of regarding transcript expression of PNPLA1 is via in silico assessments of EST clones. PNPLA1 is present in only one cDNA library, HT1080 cells treated with agents to induce random gene activation (17). In regard to adipose tissue expression, murine ATGL and adiponutrin show marked cell type specificity to adipocytes (4,22,28,73,81).…”
Section: Functional Analysis Of the Atgl Promoter Region Identifies Amentioning
confidence: 99%
“…Although many of the trapped sequences were not mapped to exons, it cannot be ruled out that many of them might be located at the sites of unknown genes. In fact, it has been demonstrated that the poly(A) trap scheme is useful for the identification of novel genes (14,35).…”
Section: Vol 23 2003mentioning
confidence: 99%